Horizon of Space and Territoriality in the Prose Narratives of Antun Šoljan - Grgas, Stipe (1998)
The article offers a reading of A. Šoljan's works using the categories of territoriality and the horizon of space. The author points to the possibility of using these categories in determining the national affiliation of the literary text.
Projekt MZOS
ENG